Good Governance and National Well-being What Are the Linkages? - Helliwell, John F.. (OECD Working Papers on Public Governance, 2014)
The paper was prepared by John F. Helliwell, Haifang Huang, Shawn Grover and Shun Wang in collaboration with Mario Marcel, Martin Forst and Tatyana Teplova. This paper has three main objectives. The first is to review existing studies of the links between good governance and subjective well-being. The second is to bring together the largest available sets of nationallevel measures of the quality of governance, and to assess the extent to which they contribute to explaining the levels and changes in life evaluations in 157 countries over the years 2005-2012, using data from the Gallup World Poll already analysed in some detail in the World Happiness Report 2013. The third objective is to use subjective well-being research to suggest ways in which governance can be changed so as to improve lives in all countries, as measured by peoples' own evaluations. The paper starts with a summary of the evidence and policy implications. There follow the four main sections of the paper, a statistical appendix containing a broad range of data and results, and an extensive annotated bibliography of empirical literature linking good governance and subjective well-being